Heavy Metal Contamination Risks in Environmental and Vegetable Samples around a Metal Workshop in Kofar Marusa, Katsina Metropolis - Kabir, H. G.; Yar’adua, A. I.; Matazu, K. I.; Lawal, R. G.; Kabir, Z. G.; Bala, M. G.; Mukhtar, M. U.; Sani, A. S.; Bashir, A.; Matazu, H. K. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt